Cryogenic and in situ characterization techniques for electrode interphase analysis - Shuang Xiang; Lin Zhu; Liang Fu; Miaomiao Wang; Xianbi Zhang; Yougen Tang; Dan Sun; Haiyan Wang (eScience)
There is an urgent need to develop innovative electrochemical energy storage devices that can offer high energy density, long lifespan, excellent rate capability, and improved security. For the electrochemical system, the electrode interphase, namely the cathode electrolyte interphase (CEI) and solid electrolyte interphase (SEI) play crucial roles in the operating mechanism, kinetics, and overall performance of the battery. However, the in-depth investigation of the unstable and complex electrode interphase is limited by the unavoidable air and moisture contact during the material transfer process and probable high-energy radiation damage in the characterization procedure. Recently, cryogenic techniques and in situ techniques have been developed and applied in the electrode interphase research to settle the radiation damage and air erosion, respectively. However, there has not been a special review that summarizes the relevant methods, so a systematic review is very important to accelerate the development. In this review, we summarize these two state-of-the-art methods, including their working principle, characterization process, advantages, and applications in electrode interphase analysis. And the integrative techniques, which are considered as the future development perspectives, are also discussed. This review can provide important directions for next-generation characterization techniques and strategies to effectively analyze the electrode interphase for advanced batteries.